Optimization Carbopol And Glycerol As Basis Of Hand Gel Antiseptics Extract Ethanol Ceremai Leaf (Phyllantus Acidus (L.) Skeels) With Simplex Lattice Design - Dwi Saryanti; Izzatun Ni'mah Zulfa (JPSCR: Journal of Pharmaceutical Science and Clinical Research, 2017)
Ceremai leaf (Phyllanthus acidus (L.) Skeels) is the one of the potential plant which contain flavonoid that had antibacterial activity. Carbopol is a gelling agent that is easily dispersible in water and provide consistency to the gel, while the glycerin is a humectant that can improve the softness of the gel. Carbopol can provide viscosity / hardness in the gel it is necessary to combine with glycerin to soften the gel and the increase of the spread The aims of this research to know the optimum composition from carbopol and gliserol in antiseptic gel formulation of ceremai leaf ethanol extract by Simplex Lattice Design (SLD). The method of extraction used maseration method with ethanol 70 % solvent. extract made of gel with components carbopol 940(0-100%) and glycerin(0-100%) with respond criteria physical properties such as pH, spreadability, sticking and protection power. The optimum formulated based on Simplex Lattice Design was the combination of carbopol 50 % : glycerol 50 %. Optimum results are obtained gel has a good physical properties. The test results showed that the effectiveness of antiseptic hand gels have generated a good antiseptic. Acceptability test results showed that the gel can be accepted by society.